2011
DOI: 10.1038/clpt.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Activity Levels of Tamoxifen Metabolites at the Estrogen Receptor and the Impact of Genetic Polymorphisms of Phase I and II Enzymes on Their Concentration Levels in Plasma

Abstract: The therapeutic effect of tamoxifen depends on active metabolites, e.g., cytochrome P450 2D6 (CYP2D6) mediated formation of endoxifen. To test for additional relationships, 236 breast cancer patients were genotyped for CYP2D6, CYP2C9, CYP2B6, CYP2C19, CYP3A5, UGT1A4, UGT2B7, and UGT2B15; also, plasma concentrations of tamoxifen and 22 of its metabolites, including the (E)-, (Z)-, 3-, and 4'-hydroxymetabolites as well as their glucuronides, were quantified using liquid chromatography-tandem mass spectrometry (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

35
341
3
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(391 citation statements)
references
References 41 publications
35
341
3
12
Order By: Relevance
“…Other enzymes involved in tamoxifen metabolism comprise CYP2C9, CYP2C19, and CYP2B6 [13]. These three enzymes are also involved in the formation of 4-OH-tamoxifen and endoxifen, but their contribution may depend on actual tamoxifen concentrations and on CYP2D6 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Other enzymes involved in tamoxifen metabolism comprise CYP2C9, CYP2C19, and CYP2B6 [13]. These three enzymes are also involved in the formation of 4-OH-tamoxifen and endoxifen, but their contribution may depend on actual tamoxifen concentrations and on CYP2D6 activity.…”
Section: Introductionmentioning
confidence: 99%
“…По разным данным, у больных гормоноположительным РМЖ при приеме тамоксифена в стандартной дозе 20 мг / сут кон-центрация 4-гидрокситамоксифена составляет 10-20 % от концентрации эндоксифена, который при-мерно в 100 раз легче связывается с рецепторами эстрогенов, чем его предшественники [13][14][15][16].…”
Section: Introductionunclassified
“…CYP2D6 activity is highly associated with TAM metabolism and may affect clinical activity. 11,12 Coincubation of TAM with potent, specific CYP2D6 chemical inhibitors such as quinidine and the antidepressant paroxetine confirmed that the inhibition of CYP2D6 activity prevents the formation of the important metabolite endoxifen. However, because TOR is less subject to CYP2D6-mediated hydroxylation, these inhibitors had little effect on the metabolism of TOR in our assays.…”
mentioning
confidence: 99%
“…1). [10][11][12] These metabolites bind to the ER with up to 30-fold greater affinity than TAM, and this increased potency for binding translates into enhanced antiestrogen activity. …”
mentioning
confidence: 99%
See 1 more Smart Citation